2015
DOI: 10.1002/ece3.1587
|View full text |Cite
|
Sign up to set email alerts
|

Lineage sorting in multihost parasites: Eidmanniella albescens and Fregatiella aurifasciata on seabirds from the Galapagos Islands

Abstract: Parasites comprise a significant percentage of the biodiversity of the planet and are useful systems to test evolutionary and ecological hypotheses. In this study, we analyze the effect of host species identity and the immediate local species assemblage within mixed species colonies of nesting seabirds on patterns of genetic clustering within two species of multihost ectoparasitic lice. We use three genetic markers (one mitochondrial, COI, and two nuclear, EF1-α and wingless) and maximum likelihood phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This scenario also offers the opportunity to test parasite/symbiont structure at hierarchical spatial scales (among host individuals, populations and communities), and make predictions on selection and adaptation processes (McCoy et al, 2001). Not surprisingly, few studies have used this multispecies and multi-scale approach (but see Johnson et al, 2002;Rivera-Parra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This scenario also offers the opportunity to test parasite/symbiont structure at hierarchical spatial scales (among host individuals, populations and communities), and make predictions on selection and adaptation processes (McCoy et al, 2001). Not surprisingly, few studies have used this multispecies and multi-scale approach (but see Johnson et al, 2002;Rivera-Parra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Parasites that colonized the Galapagos with their vertebrate hosts share patterns of distribution and evolutionary history with their hosts. Rivera-Parra et al (2015) showed that the species identity of the host was more important than sampling location for determining the phylogenetic relationships within each species of louse parasitizing two related seabird species, despite the fact that the hosts breed together in dense mixed-species colonies. However, these lice have different prevalence on different islands, demonstrating that the relationships among parasites, hosts, and islands are idiosyncratic (Rivera-Parra et al 2014).…”
Section: Co-colonization Of Hosts and Parasites: Examples From Lice And Mites On The Galapagos Flycatcher And The Galapagos Hawkmentioning
confidence: 99%
“…Cophylogeny mapping algorithms aim to map P into H, where the number of codivergence events is maximised and the map cost E is minimised (Charleston and Libeskind-Hadas 2014). Although such cost schemes may not evaluate coevolutionary scenarios exactly, particularly modelling preferential host switching (Charleston and Robertson 2002), this technique has been used to evaluate a large number of coevolutionary systems (Page 2002;Page et al 2004;Jackson and Charleston 2004;Cruaud et al 2012;Rivera-Parra et al 2015).…”
mentioning
confidence: 99%